Concurrent RAS and RAS/BRAF V600E Variants in Colorectal Cancer: More Frequent Than Expected? A Case Report - Zelli, Veronica; Parisi, Alessandro; Patruno, Leonardo; Cannita, Katia; Ficorella, Corrado; Luzi, Carla; Compagnoni, Chiara; Zazzeroni, Francesca; Alesse, Edoardo; Tessitore, Alessandra (Frontiers in Oncology, 2022)
The assessment of RAS and BRAF mutational status is one of the main step in the diagnostic and therapeutic algorithm of metastatic colorectal cancer (mCRC). Multiple mutations in the BRAF and RAS pathway are described as a rare event, with concurrent variants in KRAS and BRAF genes observed in approximately 0.05% of mCRC cases. Here we report data from patients affected by high-risk stage III and stage IV CRC and tested for RAS and BRAF mutation, being treated at our center. The analysis of KRAS, NRAS (codons 12, 13, 59, 61, 117, 146) and BRAF (codon 600) hotspot variants was performed in 161 CRC tumors from August 2018 to September 2021 and revealed three (1.8%) patients showing mutations in both KRAS and BRAF genes, including two cases with less advanced CRC and one with metastatic disease. We also identified one patient (0.6%) with a mutation in both KRAS and NRAS genes and another one (0.6%) with a double KRAS mutation. Notably, the latter was characterized by aggressive behaviour and poor clinical outcome. The mutational status, pathological features and clinical history of these five CRC cases are described. Overall, this study add evidence to the limited available literature concerning both the epidemiological and clinical aspects of CRC cases characterized by the presence of concurrent RAS/BRAF variants. Future multicentric studies will be required to increase the sample size and provide additional value to results observed so far, in order to improve clinical management of this subgroup of CRC patients.